Assessment of therapeutic benefit of antiviral therapy in chronic hepatitis C: is hepatic venous pressure gradient a better end point?. Issue 3 (1st March 2002) - Burroughs, A K; Groszmann, R; Bosch, J; Grace, N; Garcia-Tsao, G; Patch, D; Garcia-Pagan, J C; Dagher, L
Abstract : Chronic hepatitis C is a major healthcare problem. The response to antiviral therapy for patients with chronic hepatitis C has previously been defined biochemically and by PCR. However, changes in the hepatic venous pressure gradient (HVPG) may be considered as an adjunctive end point for the therapeutic evaluation of antiviral therapy in chronic hepatitis C. It is a validated technique which is safe, well tolerated, well established, and reproducible. Serial HVPG measurements may be the best way to evaluate response to therapy in chronic hepatitis C.